No correlation was observed between vitamin D levels and disability of patients with multiple sclerosis between latitudes 18° and 30° South - Fragoso, Yara Dadalti; Adoni, Tarso; Alves-Leon, Soniza Vieira; Apostolos-Pereira, Samira L.; Arruda, Walter Oleschko; Brooks, Joseph B. Bidin; Cal, Henrique S. Rodrigues; Damasceno, Carlos A. Albuquerque; Gama, Paulo Diniz; Goncalves, Marcus V. Magno; Jesus, Carlos A. da Silva de; Machado, Suzana C. Nunes; Mansur, Letícia Fezer; Matta, Andre P. da Cunha; Mendes, Maria Fernanda; Morales, Rogerio Rizo; Nobrega, Adaucto Wanderley da, Jr; Parolin, Monica K. Fiuza; Peres, Mario Pietro; Ribeiro, Marlise de Castro; Ruocco, Heloisa Helena; Scherpenhuijzen, Simone; Siquinelli, Fabio; Stoney, Patrick N.; Varela, Daniel Lima; Eboni, Audred Cristina Biondo; Spessotto, Caroline Vieira; Rocha, Elisa Teixeira da; Lacerda, Pamela Emanuele (Arquivos de Neuro-Psiquiatria, 2017)
Vitamin D has taken center stage in research and treatment of multiple sclerosis (MS). The objective of the present study was to assess the serum vitamin D levels of a large population of patients with MS and controls living in a restricted tropical area.Data from 535 patients with MS and 350 control subjects were obtained from 14 cities around the Tropic of Capricorn.The mean serum 25-OH vitamin D level was 26.07 ± 10.27 ng/mL for the control subjects, and 28.03 ± 12.19 ng/mL for patients with MS. No correlation was observed between vitamin D levels and the disability of patients over the disease duration.At least for the region around the Tropic of Capricorn, serum levels of vitamin D typically are within the range of 20 to 30 ng/mL for controls and patients with MS.
Keywords: vitamin D; multiple sclerosis; latitude